Whistleblowing: A tutela do trabalhador denunciante em Portugal - Alves, Luísa Teixeira (Anuario Coruñés de Derecho Comparado del Trabajo, 2022)
The present essay, after highlighting the antecedents of the European Directive that deals with the protection of whistleblowers, analyzes the essential aspects of this instrument, comparing it with the law that, in Portugal, proceeded to its transposition into the national legal system. The incipient jurisprudential elaboration of the subject in Portugal is also assessed, despite the existence of international instruments, binding for this State, in which the fundamental principles and guidelines to be followed in the approach to the matter were already enshrined. The basic inference that the study makes possible is the insufficiency of the established legal regime, for the accomplishment of the protection objectives defined by the Directive and its international antecedents.